Tool-use - Beattie, David; Oonagh Young Gallery, Dublin ([S.l.] : [the artists and writer], 2011)
Edwards, Sean ; Harle, Matt ; Keogh, Sam ; Thompson, Adam ; Yao, Amy
Publicatie n.a.v. de tentoonstelling 'Tool-use' in de OOnagh Young Gallery te Dublin, 18.06.2011-29.07.2011
boek